Squamous cell carcinoma with hepatic metastasis in a saltwater crocodile (Crocodylus porosus). Issue 3 (March 2016) - Hill, AG; Denis, MM; Pyne, M
Abstract : Background: Squamous cell carcinomas (SCC) are uncommon in reptiles and there have been few reports of neoplasia in Australian crocodiles, despite increased numbers being raised in captivity. Case report: We report a locally invasive SCC in the hindlimb of a wild‐caught saltwater crocodile ( Crocodylus porosus ) with hepatic metastasis. The gross appearance was soft tissue swelling adjacent to the nail bed, progressing to abscessation incorporating multiple toes. Diagnosis was achieved by biopsy during amputation of the affected toes. Hepatic metastasis was identified at necropsy, with a similar gross appearance resembling an abscess. Clinical significance: Neoplasia is an uncommon finding in crocodilians and metastatic neoplasia is rarely documented. This is the first report of SCC in a crocodilian.